PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE PAIR CHECKS DISERTAI KUIS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 13 PADANG - -, Marlina - (Pendidikan Matematika, 2014)
This research is based on the low mathematical concept comprehension ofstudents. The purpose of this research is to know the effect of applyingcooperative learning model with pair checks type and quiz with mathematicalconcept of students. The type of research is pre-experiment with one-shot casestudy of research framework. The instrument of research is essay with rediabilityr11 = 0,96. The technique of data analysis which is used is descriptive analysis.Based on the result of the research the average score of quis in every meeting is88,52 in quiz 1, 94,55 in quiz II, 98,72 in quiz III, 98,77 in quiz IV and theaverage score of the result before having treament is 54,67 and after havingtreament is 82,42. So, it was concluded that the application of cooperativelearning model with pair checks type and quis with mathematical conceptcomprehesionof second grade Junior High School 13 Padang Students.